Matrix Stiffness Regulates the Osteogenic Differentiation of hPDLSCs via DNA Methylation - Rong Ding; Chen Chen; Ling Wang; Yijie Wang; Zhen Chai; Siyu He; Qianqian Zhang; Shuli Cheng; Rui Zou (International Dental Journal)
Objectives: This study aimed to examine the influence of matrix stiffness on osteogenic differentiation via epigenetic mechanisms in human periodontal ligament stem cells (hPDLSCs), with implications for understanding orthodontic tooth movement. Materials and Methods: hPDLSCs were cultured on substrates with varying stiffness (soft and stiff). Dot blot and immunofluorescence techniques were employed to measure global DNA methylation levels. RT-qPCR and alkaline phosphatase (ALP) activity assays were conducted to assess differences in DNA methylation and osteogenic potential. Additionally, ELISA was used to quantify DNA methyltransferase content and activity. Results: hPDLSCs on stiffer substrates exhibited increased 5-methylcytosine (5-mC) and higher global DNA methylation levels than those on soft substrates. With increased matrix stiffness, DNMT3A and DNMT3B mRNA expression levels rose. hPDLSCs on stiff matrices also showed elevated DNMT3B enzyme content and osteogenic activity. When global DNA methylation was reduced, mRNA levels of RUNX2, ALP, and Col-1 decreased, along with a notable reduction in ALP staining intensity in the inhibitor group. Conclusions: Matrix stiffness is positively associated with global DNA methylation, with DNMT3B likely mediating this regulation in hPDLSCs. Furthermore, DNA methylation levels are positively linked to the osteogenic capability of hPDLSCs.